2014
DOI: 10.1038/ncomms4743
|View full text |Cite
|
Sign up to set email alerts
|

AmotL2 links VE-cadherin to contractile actin fibres necessary for aortic lumen expansion

Abstract: The assembly of individual endothelial cells into multicellular tubes is a complex morphogenetic event in vascular development. Extracellular matrix cues and cell-cell junctional communication are fundamental to tube formation. Together they determine the shape of endothelial cells and the tubular structures that they ultimately form. Little is known regarding how mechanical signals are transmitted between cells to control cell shape changes during morphogenesis. Here we provide evidence that the scaffold prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 58 publications
5
84
0
Order By: Relevance
“…Changes in the actin cytoskeleton have a major impact on the morphology and stability of VE-cadherin-based cell-cell junctions (Hultin et al, 2014;Noda et al, 2010;Phng et al, 2015;Sauteur et al, 2014;Schulte et al, 2011), in part by altering the magnitude and direction of the forces that are exerted on cell-cell junctions (Oldenburg and de Rooij, 2014). Distinct types of cell-cell junctions exist depending on the organization of the junctionassociated actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the actin cytoskeleton have a major impact on the morphology and stability of VE-cadherin-based cell-cell junctions (Hultin et al, 2014;Noda et al, 2010;Phng et al, 2015;Sauteur et al, 2014;Schulte et al, 2011), in part by altering the magnitude and direction of the forces that are exerted on cell-cell junctions (Oldenburg and de Rooij, 2014). Distinct types of cell-cell junctions exist depending on the organization of the junctionassociated actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Primary antibody diluted in blocking buffer was incubated at room temperature for 1 h. The following commercial antibodies were used; Par3 (1:100, Millipore), Trappc9 (1:25, Genetex), p100 AmotL2, Trappc10 (1:100, 1:50, Santa Cruz Biotechnology), ZO1 ( . Immunoaffinity-purified rabbit polyclonal antibodies against the C-terminal 20 amino acids of human AmotL2 was used in paraffin sections have been previously described (Hultin et al) 18 . For Amotl2, antibodies were also made against the epitope NH2-CQKAPSAVDLFKGVDDVSAE-COOH cross-reactive with human and zebrafish Amotl2.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that each member has a distinct role in blood vessel formation in that Amot controls migration, AmotL1 junction formation and AmotL2 aortic lumen expansion [16][17][18] . Acting as a scaffold protein, AmotL2 and its related proteins associate and join together proteins involved in junction formation, apical polarity and actin cytoskeleton 19 .…”
mentioning
confidence: 99%
“…43 They additionally show that this interaction is required for the opening of the vascular lumen during vascular development. Yamamoto and colleagues revealed the importance of b1-integrins in the stabilization of cell-cell junctions.…”
Section: Introductionmentioning
confidence: 97%